2006
DOI: 10.1016/j.clpt.2006.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Lopinavir/ritonavir reduces lamotrigine plasma concentrations in healthy subjects

Abstract: Lopinavir/ritonavir decreases the AUC of lamotrigine, probably by induction of glucuronidation. A dose increment to 200% of the initial lamotrigine dose is needed to achieve concentrations similar to those with lamotrigine alone. Lamotrigine does not appear to affect the pharmacokinetics of lopinavir/ritonavir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 26 publications
0
42
0
Order By: Relevance
“…Drug-drug interactions in HIVassociated pain management are not restricted only to opioids; concomitant administration of lopinavir/ritonavir caused a 46% reduction in the plasma concentrations of lamotrigine, which is an antiepileptic recommended as second or third line drug for the treatment of neuropathic pain [6]. The mechanism behind this interaction might be the induction in lamotrigine glucuronidation [48]. Theoretically, the induction of glucuronidation could have an influence on the metabolism of oxycodone and its metabolites, but these metabolic routes are of minor importance [49] and they were not investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Drug-drug interactions in HIVassociated pain management are not restricted only to opioids; concomitant administration of lopinavir/ritonavir caused a 46% reduction in the plasma concentrations of lamotrigine, which is an antiepileptic recommended as second or third line drug for the treatment of neuropathic pain [6]. The mechanism behind this interaction might be the induction in lamotrigine glucuronidation [48]. Theoretically, the induction of glucuronidation could have an influence on the metabolism of oxycodone and its metabolites, but these metabolic routes are of minor importance [49] and they were not investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to inhibition, interactions with glucuronidation can occur through induction of UGT enzymes. Studies have reported that rifampicin and lopinavir/ritonavir induced lamotrigine glucuronidation, which required a doubling of the dose to maintain a therapeutic plasma concentration [34,35]. These examples show that drug-drug interactions through modulation of glucuronidation can be clinically significant.…”
Section: Glucuronidation As a Pathway For Drug Interactionsmentioning
confidence: 99%
“…80 However, the antiretroviral drugs lopinavir and ritonavir decrease lamotrigine plasma levels. 81 Carbamazepine is an inducer of CYP3A enzymes and may increase the metabolism of the antiretroviral drugs indinavir and delavirdine. 47 On the other hand, ritonavir may raise the serum levels of carbamazepine.…”
Section: Maniamentioning
confidence: 99%